2016
DOI: 10.1177/1479164116653342
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is associated with adverse structural and functional cardiac remodelling in chronic heart failure with reduced ejection fraction

Abstract: Diabetes mellitus is associated with features of adverse structural and functional cardiac remodelling in patients with chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
(27 reference statements)
2
25
1
5
Order By: Relevance
“…Similarly, results from the CHARM program showed increased rates of hospitalisation in those patients with CHF and diabetes compared to those without diabetes (8). More recently, we have shown that diabetes is associated with features of adverse structural and functional cardiac remodelling in CHF with reduced ejection fraction (10). In this study, diabetes resulted in worse renal function, lower haemoglobin and more symptomatic heart failure.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Similarly, results from the CHARM program showed increased rates of hospitalisation in those patients with CHF and diabetes compared to those without diabetes (8). More recently, we have shown that diabetes is associated with features of adverse structural and functional cardiac remodelling in CHF with reduced ejection fraction (10). In this study, diabetes resulted in worse renal function, lower haemoglobin and more symptomatic heart failure.…”
mentioning
confidence: 59%
“…Unfortunately, SCD in patients with diabetes and CHF is not addressed in the majority of the major guidelines (9). In another study we have shown that those with diabetes have a higher prevalence of co-morbidities, however diabetes was independently associated with increased mortality (10). In a recent issue of JACC, Johansson et al analysed 35,163 patients in the Swedish Heart Failure Registry (SwedeHF) comparing type 2 diabetes mellitus in both ischaemic and non-ischaemic CHF (11).…”
mentioning
confidence: 99%
“…Высокий уровень глюкозы и жиров при СД 2, преобладание окисления жирных кислот (ЖК) негативно влияют на степень окисления глюкозы при СД 2. Диабетическое сердце почти полностью переключается на окисление ЖК в митохондриях (Мх) для продукции аденозинтрифосфата при резком снижении инсулинзависимого поглощения глюкозы -состояние, получившее название «метаболическая жесткость», интимные патогенетические механизмы развития которой остаются неизвестными [1][2][3]. Было показано, что гипергликемия per se может быть триггером клеточного поражения независимо от утилизации ЖК, например в эндотелиальных клетках [4].…”
Section: Introductionunclassified
“…Было показано, что гипергликемия per se может быть триггером клеточного поражения независимо от утилизации ЖК, например в эндотелиальных клетках [4]. Постоянная диабетическая гипергликемия как состояние с нарушением метаболизма глюкозы прежде всего ведет к нарушению редокс-баланса и подачи электронов для синтеза аденозинтрифосфата в дыхательной цепи Мх и в процессах гликолиза, а снижение редокс-потенциала, отношения никотинамидаденин динуклеотида (НАД) к восстановленной форме (НАДН) -НАД / НАДНвследствие накопления НАДН, является триггерным механизмом оксидативного стресса и развития многих метаболических синдромов [2,[5][6][7][8][9]. Имеется очень мало данных о взаимосвязи между гипергликемией, утилизацией ЖК, уровнем гликилированного гемоглобина (HbA1c) и состоянием систем редокс-гомеостаза крови, миокарда, почек при СД 2.…”
Section: Introductionunclassified
“…2,3 Moreover, cardiac magnetic resonance imaging is beginning to elicit additional abnormalities of cardiac structure and function in people with diabetes. 4 The paper from Walker et al 5 describes the results from the study of 628 unselected patients with heart failure of whom 25% had a known diagnosis of diabetes. The results confirmed the adverse risk profile associated with increased mortality in diabetes patients with heart failure and identified evidence of increased pulmonary artery pressure and pulmonary oedoma, and less favourable LV remodelling compared to the non-diabetes cohort.…”
mentioning
confidence: 99%